PENGARUH WHATSAPP BERBASIS GOOGLE CLASSROOM DAN GOOGLE MEET DENGAN IMPLEMENTASI MODEL INQUIRY LEARNING DALAM PEMBELAJARAN FISIKA TERHADAP HASIL BELAJAR SISWA - Muliyana S Nupura; Mursalin Mursalin; Abd Wahidin Nuayi; Asri Arbie (Universitas Negeri Gorontalo, 2021)
This study aims to determine the significant effect of WhatsApp based on Google Classroom and Google Meet with the implementation of the inquiry learning model in physics learning on student learning outcomes. The research was conducted during the Covid-19 pandemic with a DARING learning process, the method used was the pre-experimental method with one group pretest-posttest design. This research was conducted at SMA Negeri 1 Suwawa in the academic year 2020/2021 using saturated sampling technique and random selection of classes, obtained by students of class XI IPA 1 as an experimental class, class XI IPA 3 as replication class 1, XI IPA 4 as class replication 2 and class XI IPA 2 as replication class 3. The research instrument is in the form of an essay test of 8 numbers on the Dynamics of Rotation and Sturdy Object Balance with a KKM of 73. Based on the results of hypothesis testing, it is known that the t value for each experimental class is replication class 1, replication class 2, and replication class 3 are 4.16, 3.089. , 3.19, 3.386 greater than t table 1.705, 1.739, 1.71, 1.72, it can be concluded that there is a significant positive effect of treatment. Based on the analysis of the N-Gain and the effect size, the N-Gain value for the four classes, respectively, is 0.61, 0.59.0.59, and 0.62 in the medium category, for the effect size value is 1.9 with strong effect interpretation. This shows that there is consistency in the treatment given to student learning outcomes.